Barbados : Sectoral Balance Sheet Mismatches and Macroeconomic Vulnerabilities - Yartey, Charles Amo (IMF Working Papers; Working Paper, 2012)
This paper uses the balance sheet approach to analyze macroeconomic vulnerabilities in Barbados between 2006 and 2009. It discusses the financial position of the economy and its main sectors and the sectors' exposure to changes in exchange rates. The main finding of the analysis is that the balance sheet of the aggregate economy has been weakened by the recent deterioration in the balance sheet of the nonfinancial public sector. Macroeconomic vulnerabilities have increased in Barbados since 2006 due to the high public debt and the deterioration in the net financial position with nonresidents. The private sector, however, maintained a healthy position and seems resilient to shocks. The paper also finds the balance sheet of the nonfinancial public sector has deteriorated significantly reflecting weak fiscal performance. While the central government is highly vulnerable to exchange rate shock, debt rollover risks are likely to be limited since most of external liabilities are long term and most domestic liabilities are held by the National Insurance System.